2013
DOI: 10.4028/www.scientific.net/amm.315.941
|View full text |Cite
|
Sign up to set email alerts
|

Palm Fatty Acid Distillate as an Alternative Source for Hydraulic Oil

Abstract: This study investigates the physical properties of pure palm fatty acid distillate (PFAD) as a new, clean and renewable source of lubricant and hydraulic oil. This study is done using a four-ball tribotester. The experiments are conducted at five different temperatures of 55, 75, 95, 105 and 125 °C. The rotational speed was fixed at 1200 rpm, normal load was 40 kg and duration was 1 hour. For evaluating the results, all experiments again were conducted using commercial engine mineral and hydraulic mineral oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…RESEARCH There were also studies that had shown the palm-based oil as having comparable lubricating properties like those of the commercial engine oil [9,10]. Among the studies that were conducted on its development as a bio-lubricant had included those of Syahrullail et al, where they had investigated its characteristics to be used as a metal forming lubricant as well as Bari et al, who had studied its possible niche as an engine diesel and hydraulic fluid [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…RESEARCH There were also studies that had shown the palm-based oil as having comparable lubricating properties like those of the commercial engine oil [9,10]. Among the studies that were conducted on its development as a bio-lubricant had included those of Syahrullail et al, where they had investigated its characteristics to be used as a metal forming lubricant as well as Bari et al, who had studied its possible niche as an engine diesel and hydraulic fluid [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These results surely contributed to the high VI, because the high VI is related to the small changes in viscosity with the changes in temperature. 43 It can be observed that the VI of PKO + CG nanolubricant in Table 4 increased by about 32.6% compared to that of PKO base lubricant. The addition of nanoparticles to PKO base lubricant resulted in a more stable viscosity over a wide temperature range, which is likely due to stronger intermolecular interactions between oil molecules and nanoparticles.…”
Section: Kinematic Viscosity Of Nanolubricantsmentioning
confidence: 90%
“…The studies were carried out for 60 min at 75°C with a rotating speed of 1200 rpm and an applied load of 392 N. These parameters were selected using the ASTMD4172 standard method. 33 Before and after each experiment, the steel balls were properly cleaned with acetone and replaced. The friction torque was recorded during the test, and the coefficient of friction (COF) can be retrieved immediately from the data acquisition system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers have investigated the characteristics of palm oil in a metal forming lubricant [5]. Besides that, palm oil was also investigated to be used as diesel engine and hydraulic fluid [6]. There are four major groups of palm oil that have been investigated by researchers around the world; namely using 100% palm oil as a test lubricant [7], palm oil with additives [8] and palm oil with nano particles [9].…”
Section: Introductionmentioning
confidence: 99%